Access to reproductive health services by female survivors of sexual gender-based violence: a descriptive cross-sectional study of Nairobi City County, Kenya - Oredo, Pascal O.; Kimani, Harun M.; Mugo, Judy (International Journal Of Community Medicine And Public Health, 2024)
Background: Sixty percent of women globally are exposed to reproductive health problems related to sexual gender-based violence. In Kenya, sexual violence is one of the top 10 risk factors for disease burden. The study aimed to determine access to reproductive health services by female survivors of sexual gender-based violence in Nairobi city county, Kenya. Methods: The study adopted descriptive cross-sectional design using pretested questionnaires. Study population was 269 female survivors of sexual gender-based violence. Data was analysed thematically and presented by use of percentages and frequencies distribution tables. Binary logistic regression model was used to determine relationships between dependent and independent variables. Odds ratios were evaluated for significance by considering the 95% confidence interval at p value ≤0.05. Results: Access to reproductive health services by female survivors of sexual gender-based violence was 26%. Service availability for survivors in the facilities had a 3 times likelihood of access sexual, knowledge on failure to seek immediate medical attention had 4 times likelihood to increase access while awareness of the period to have prophylaxis had 4.66 times likelihood to increase access. Services provided to survivor had 39% likelihood to increase access, survivors screened for sexually transmitted disease before admission had 10% more likelihood to access and survivors who received post exposure prophylaxis had 0.62 times likelihood of access to sexual reproductive health services. Conclusions: Availability of comprehensive sexual reproductive health services at the facility and good knowledge would increase access to reproductive health services.